PELATIHAN PENINGKATAN NILAI TAMBAH JAGUNG DARI PENGOLAHAN HINGGA PEMASARAN DIGITAL BAGI KELOMPOK TANI HARAPAN JAYA DI DESA BALATA DUA PARBALAN - Sitorus, Peniel Sam Putra; Situmorang, Eduward; Sirait, Gloria; Sianipar, Vina; Adolf MS, Albert; Desmon Sirait, Glenn; Junita Arista Siringoringo, Kerin; Sitorus, Maria; Sitorus, Pontas (Yayasan Nusantara Hasana Berdikari, 2025)
Simalungun Regency has 32 sub-districts covering an area of 438,660 hectares, representing 6.12% of the total area of North Sumatra province. There are 386 villages (nagori) and 27 sub-districts (kelurahan). In Pematang Bandar District, corn and rice are commonly cultivated. In Balata Village, Jorlang Hataran District, farmers are organized into the